Therapeutic effects of progesterone and its metabolites in traumatic brain injury may involve non-classical signaling mechanisms - Cooke, Paul S. (Frontiers in Neuroscience, 2013)
Traumatic brain injury is an important and costly medical problem for which no clinically proven treatment currently exists. Studies in rodents and humans have shown beneficial effects of progesterone (P4) on both mortality and functional outcomes following TBI. Neuroprotective effects of P4 in TBI likely involve the classical nuclear progesterone receptors (Pgr) that are widely distributed in both glial cells and neurons of the brain. However, P4 may have critical effects not mediated through Pgr. In the brain, P4 is converted to a metabolite, allopregnanolone (ALLO), whose beneficial effects equal or exceed those of P4 in TBI. ALLO does not bind Pgr, suggesting it acts through non-classical pathways. ALLO has effects on GABAA and pregnane X receptors, as well as on the mitochondrial permeability transition pore. In addition, ALLO is metabolized to another compound, 5alpha-dihydroprogesterone, which binds Pgr, suggesting ALLO actions may involve signaling through Pgr as well as the aforementioned mechanisms of action. P4 and ALLO also signal through a number of membrane receptors (progesterone receptor membrane component 1, and membrane progesterone receptors alpha, beta, gamma, delta and epsilon) in the brain that are distinct from Pgr, although the role of these receptors in the normal brain and in the therapeutic response to P4 and ALLO following TBI is unclear. In summary, P4 has the potential to become the first clinically effective treatment for TBI, and the effects of P4 and its metabolite ALLO in TBI may involve Pgr, membrane progesterone receptors and other signaling pathways. Elucidating these mechanisms will more clearly reveal the potential of classical and non-classical pathways to mediate important effects of P4 and its metabolites, and potentially offer new therapeutic approaches to TBI.